Ways of constitution-making in Southeast Asia: actors, interests, dynamics - Croissant, Aurel (Contemporary Southeast Asia, 2014)
This article analyses eleven cases of constitution-making in eight Southeast Asian countries since 1986. It investigates design choices and actors’ interests, the link between the form of the political regime and the extent to which process designs matter for the legitimacy of the constitutional orders in the region. In doing so, the article demonstrates that the link between the form of the political regime and the extent to which constitution-making is inclusive or participatory is less clear-cut. While we would expect better opportunities for public participation and broader inclusion of extra-parliamentary actors in constitution-making in democratic environ-ments, the empirical evidence is mixed. If and how this matters for public support for a constitution and the social acceptance for the constitutional order is not clear. In fact, the Southeast Asian experience seems to indicate that procedural legitimacy is less relevant for the acceptance of a constitution than the legitimacy that derives from the “day-to-day plebiscite” by citizens and elites. (Contemp Southeast Asia/GIGA)
Keywords: Südostasien